Säkerhetsklimat inom Piteå kommun - Klepic, Jovana (2012)
To ensure that Piteå Municipality's Policy and Guidelines for safety are complied to, the municipality wishes to examine the current safety climate among employees within the municipality. The purpose of this thesis is to examine how risks are perceived among employees and whether the risks identified in the administrations are evaluated in terms of the municipality's action plan concerning safety. The following questions are posed: What risks can the employees identify within their own administration? Are any of them included in the municipality's safety action plan? How do the employees perceive policies, procedures, and practical safety work? Can the employees' perception of risk and security impact on the municipality's long-term security? A survey with 79 employees in Piteå was conducted by means of the Nordic Safety Climate Questionnaire (NOSACQ-50) with some additional questions included. The results indicate that Piteå had a strong safety climate with a NOSACQ-50 value >3.30. There was, however, a lack of knowledge regarding the content of the action plan and the guidelines for safety. The employees did identify several risks both mental and physical not included in the action plan such as threat, violence, and working alone. How employees' perception of risk and safety can affect the municipality's long-term safety may depend on whether the employees can identify risks within their workplace, since good safety awareness also is a prerequisite for safe behavior.Keywords: safety climate, organization climate, risk, risk perception Validerat; 20121126 (global_studentproject_submitter)